Sectoral trade effects of heterogeneous environmental provisions in trade agreements: Exploring the margins - Petros Suzgo Kayovo Mkandawire; Dela-Dem Fiankor; Inmaculada Martínez-Zarzoso; Bernhard Brümmer (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
The ubiquity of environmental provisions in trade agreements is well documented, but their economic effects are largely inconclusive. This article analyzes whether environmental provisions in preferential trade agreements (PTAs) have differential effects on sectoral trade. It further examines whether these effects depend on the heterogeneity of environmental provisions and exporters' level of development and quality of regulation. We exploit two finegrained panel datasets on product-level bilateral trade flows for nearly 200 countries and 300 different types of environmental provisions contained in 775 PTAs for the period 1996 to 2021. We use a theory-consistent industry-level structural gravity model and Pseudo Maximum Likelihood estimator to estimate the trade effects of PTAs with environmental provisions. We use a three-way fixed effects approach to control for unobserved heterogeneity and potential reverse causality. Overall, we find that environmental provisions do not reduce export values and volumes, but their effects are heterogenous across sectors and exporters' income levels and regulatory quality. These effects also depend on the number and types of environmental provisions included in PTAs (i.e., design of PTAs). We also find that exporters' level of income and quality of regulation moderate the trade effects of environmental provisions. We show that the trade effects of environmental provisions are more pronounced in developing exporting countries and/or those that have weak regulatory quality. Moreover, environmental provisions affect export values through their relatively larger effects on the intensive export margin. We show that environmental provisions in PTAs can be used as targeted trade policy strategy to jointly promote economic and environmental sustainability. Our results demonstrate the importance of assessing the effects of targeted trade policies at disaggregated level to capture heterogeneity and enhance formulation of trade policies and achieve sustainable development.
Keywords: F14; Q56; F18; F13; 330; International trade; trade agreements; environmental provisions; structural gravitymodel; environment; trade margins